Facilitation of fracture repair using low-intensity pulsed ultrasound - Warden, S. J.; Wong, W. T.; Bennell, K. L.; McMeeken, J. M.; Wark, J. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
A recent application of ultrasound (US) therapy is to bone fractures. In two randomized controlled trials in humans, specific dosed US accelerated fresh tibial and radial fracture repair by 38%. When applied to delayed- and non-unions the same dosed US resulted in union in over 80% of cases. Similar US may augment fracture repair in veterinary practice. This paper reviews US dosages applied during fracture repair and their effect on bone healing. It concludes by discussing the clinical and practical implications of these findings to veterinary practice and the need for further research into this electrotherapeutic modality.Low-intensity pulsed ultrasound has been shown to facilitate fresh fracture repair, reduce the incidence of delayed-union and initiate healing of fractures displaying delayedand non-union. This paper discusses these findings and their implications to veterinary practice.
Keywords: Fracture healing; ultrasound therapy